Lifestyle determinants of diabetes mellitus amongst people living with HIV in the Eastern Cape province, South Africa - Nokwanda E. Bam; Wezile Chitha; Jafta Ntsaba; Sibusiso C. Nomatshila; Teke Apalata; Sikhumbuzo A. Mabunda (AOSIS, 2022)
Background: Type 2 diabetes mellitus (DM) has serious consequences for those affected. Little is documented on the lifestyle determinants of type 2 DM in people living with human immunodeficiency virus (PLWHIV). Aim: This study aimed to assess the lifestyle determinants of type 2 DM amongst PLWHIV who were on antiretroviral treatment (ARV). Setting: This study was undertaken in 10 community health clinics and 140 clinics in South Africa's Eastern Cape province. Methods: This case control study was undertaken amongst PLWHIV who were on ARV in OR Tambo district. Results: Cases and controls showed statistically significant differences on the duration of time on ARV (p  0.0001), vigorous work (p = 0.019), participation in moderate sport (p = 0.007) and consuming daily fruit and vegetable servings (p = 0.021). Those reporting to be on ARVs for 6 to 10 years were three times more likely to be diabetic than those who had only been on ARV for a year or less (odds ratio [OR] = 3.0; p = 0.017) and in comparison, to participants who reported having one serving, participants who had four fruit and vegetable servings daily were 3.2 times more likely to be diabetic (OR = 3.2; p = 0.002). Conclusion: This study revealed significant nutritional imbalances on fruit and vegetable servings and on participation in moderate sport resulting in poor diabetic control. Routine screening and measurements need to focus on dietary and physical lifestyle determinants of type 2 DM in order to counsel patients on ARV on balanced nutrition and optimise outcomes in the quality care of PLWHIV.